The Impact of Economic Policies on Churches and Faith-Based Organisations in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The economic policies of the Tinubu-led administration, including subsidy removal, naira floating, and fuel taxation, were enacted in 2023 with the aim of stimulating economic growth through the attraction of foreign investors and increased government revenue. However, the timing of these policies has proven problematic, as they were implemented when the country was already grappling with significant macroeconomic challenges such as inflation, low government revenue, high budget deficits, and increased foreign debt. This paper examines the multifaceted impact of these economic policies on churches and faith-based organisations in Nigeria. It explores how these policies affect the operational sustainability, social outreach, and financial structures of these religious institutions. Drawing on case studies, media reports, and policy documents, the study highlights how economic shifts can constrain faith-based organisations' ability to provide welfare services, fund missions, and maintain infrastructure. It also considers the adaptive strategies employed by churches, including financial restructuring, increased emphasis on stewardship, and strategic partnerships. The paper submits that there is a strong connection between government economic policies and the operational sustainability, social outreach, and financial structure of churches and faith-based organisations in Nigeria.